2012
DOI: 10.1093/nar/gks1136
|View full text |Cite
|
Sign up to set email alerts
|

Reverse engineering a mouse embryonic stem cell-specific transcriptional network reveals a new modulator of neuronal differentiation

Abstract: Gene expression profiles can be used to infer previously unknown transcriptional regulatory interaction among thousands of genes, via systems biology ‘reverse engineering’ approaches. We ‘reverse engineered’ an embryonic stem (ES)-specific transcriptional network from 171 gene expression profiles, measured in ES cells, to identify master regulators of gene expression (‘hubs’). We discovered that E130012A19Rik (E13), highly expressed in mouse ES cells as compared with differentiated cells, was a central ‘hub’ o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 80 publications
4
36
1
Order By: Relevance
“…We found 1148 genes whose expression levels were altered by 2-fold or more in KO cells expressing WT EPOP vs. KO cells. These genes are associated with transcription, development and axon guidance (Table S1), similar to what has been described before (De Cegli et al, 2013). Gene set enrichment analysis (GSEA) revealed that PRC2 targets were significantly de-repressed independently of the interaction with Elongin BC (Figure 6B), consistent with our finding that Elongin BC is not required for EPOP to inhibit PRC2, and explains the partial but significant overlap of affected genes in WT versus the mutant EPOP-expressing cells (Figure 6C).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…We found 1148 genes whose expression levels were altered by 2-fold or more in KO cells expressing WT EPOP vs. KO cells. These genes are associated with transcription, development and axon guidance (Table S1), similar to what has been described before (De Cegli et al, 2013). Gene set enrichment analysis (GSEA) revealed that PRC2 targets were significantly de-repressed independently of the interaction with Elongin BC (Figure 6B), consistent with our finding that Elongin BC is not required for EPOP to inhibit PRC2, and explains the partial but significant overlap of affected genes in WT versus the mutant EPOP-expressing cells (Figure 6C).…”
Section: Resultssupporting
confidence: 75%
“…C17orf96, esPRC2p48 and E130012A19Rik) (GeneID: 103551 (mouse); 100170841 (human))(UniprotID: Q7TNS8 (mouse); A6NHQ4 (human)) has recently been identified as an interacting partner of the mammalian PRC2 (Alekseyenko et al, 2014; De Cegli et al, 2013; Smits et al, 2013; Zhang et al, 2011) but its role and mechanism of action are poorly understood. It is highly expressed in ES cells, during embryogenesis and in the adult brain (Liefke and Shi, 2015) and has been proposed to contribute to somatic cell reprogramming (Zhang et al, 2011) and neuronal differentiation (De Cegli et al, 2013). We have found that EPOP represses PRC2 function in vivo, possibly by interfering with PRC2 chromatin binding via the interaction of its C-terminal region with the VEFS box of SUZ12 (Liefke and Shi, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used 342 embryonic stem cell-specific genes that are both in our study and in the list of 543 genes ( F D R <.025) in [16]. There are 161 and 181 genes in each state.…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, among the enriched EZH2 interactions we found two relatively uncharacterized human proteins: C10orf12, reported to be ubiquitously expressed (http://biogps.org/gene/26148/), and C17orf96, a potential homolog of mouse E13 (E130012A19Rik) protein implicated in epigenetic regulation of neuronal differentiation (15). C10orf12 and C17orf96 lack apparent homologs in Drosophila, but are conserved from bony fishes to humans, without discernible protein domains suggestive of their possible functions in the complex.…”
Section: Significancementioning
confidence: 99%